Culture and motivation drive airport health performance - Yuni Pratikno; Vica Harahap; Naik Henokh Parmenas; Rubadi Rubadi; Karnawi Kamar (Goodwood Publishing, 2025)
Purpose: This study examines how organizational culture and work motivation affect employee performance at the International Airport Class I Port Health Office (Terminal 3), and identifies practical implications for improving public health service delivery. Research Methodology: A quantitative, descriptive design was applied using saturated sampling (census) of 66 Terminal 3 employees. Data were collected via questionnaires and analyzed with multiple linear regression in SPSS, supported by validity, reliability, and classical assumption tests. Results: Organizational culture significantly influences employee performance, and work motivation also shows a positive and significant effect. Simultaneously, culture and motivation jointly predict performance, indicating that stronger cultural alignment and higher motivation are associated with better employee outcomes. Conclusions: Improving performance in the airport health service context requires reinforcing a supportive organizational culture and strengthening employee motivation, as both factors work together to enhance performance. Limitations: The study is limited to one unit (Terminal 3) with a relatively small population and relies on self-reported questionnaire data; broader contextual factors (e.g., teamwork, punctuality pressures, service load) may not be fully captured. Contribution: The findings provide actionable recommendations to develop or refine SOPs related to organizational culture and motivation, supporting leadership policy implementation, daily operational effectiveness, and improved service performance in airport health offices.